Potential of rhizobacteria in the control of Fusarium solani (Mart.) Sacc. in cucumber (Cucumis sativum L.) (Scientia Agricola, 1995)
Rhizobacteria, isolated from the rhizosphere of different hosts were selected in vitro, based on the antagonism against Fusarium solani, agent of root rot. In vitro, 18 bacterias were selected from rhizosphere of healthy plants of cucumber and, from those, only three were efficient in inhibiting the micelial growth of the pathogen. In these tests two isolates of Bacillus subtilis (0G and 5G), and two of Pseudomonas (CBPN and St Barb.), antagonistic to some pathogenic fungi, were included. These bolates also inhibited the growth of F solani. The bolate OG of B. subtilis reduced significantly the root rot of cucumber. Beneficial effects were obtained with the bolates St Barb., 0G and CBPN in relation to plant growth.